The role of phosphoenolpyruvate in the simultaneous uptake of fructose and 2-deoxyglucose by Escherichia coli. - Kornberg, H (1994)
Nonmetabolizable glucose analogs inhibit the growth of Escherichia coli on a wide variety of carbon sources. This phenomenon was investigated with particular reference to the effect of 2-deoxyglucose (2DG) on growth on fructose as sole carbon source. When the inhibitor is supplied in sufficiently low concentrations, the initial arrest of growth is overcome; this relief of inhibition is aided by means that increase the availability of phosphoenolpyruvate (PEP) to the growing cells, such as the use of L-aspartate instead of ammonium chloride as sole nitrogen source for growth, and the introduction of the pps+ allele into a pps- strain. Studies with [14C]2DG showed that the analog or its 6-phosphate as such did not inhibit growth but that 2DG exerted its effect by competing for intracellular PEP and lowering its concentration below that needed to sustain growth. Direct measurements of the PEP-dependent phosphorylation of 2DG and of fructose by permeabilized E. coli showed that the apparent Km for PEP was nearly 7 times higher for 2DG that it was for fructose, although the apparent Vmax for 2DG was nearly 3 times that for fructose; this explains the ability of cells to overcome the inhibition by low, but not by high, concentrations of 2DG.